2004
DOI: 10.1111/j.1365-2265.2004.02094.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury and subarachnoid haemorrhage are conditions at high risk for hypopituitarism: screening study at 3 months after the brain injury

Abstract: TBI and SAH are conditions associated with high risk of acquired hypopituitarism. The pituitary defect is often multiple and severe GHD is the most frequent defect. Thus neuroendocrine evaluations are always mandatory in patients after brain injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
298
4
8

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 309 publications
(330 citation statements)
references
References 28 publications
20
298
4
8
Order By: Relevance
“…Taken together, these observations suggest that cortical TBI inflicts long-lasting destructive changes in brain tissue that is remote from the site of the initial CCI. Specifically, our findings and others in humans with TBI (Kelly et al, 2000;Lieberman et al, 2001;Agha et al, 2004a;Aimaretti et al, 2004;Bondanelli et al, 2004) demonstrate that cortical TBI can have substantial effects on the expression of the GH system, supporting clinical studies and replicating the results in an animal model of CNS injury.…”
Section: Kasturi and Stein Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Taken together, these observations suggest that cortical TBI inflicts long-lasting destructive changes in brain tissue that is remote from the site of the initial CCI. Specifically, our findings and others in humans with TBI (Kelly et al, 2000;Lieberman et al, 2001;Agha et al, 2004a;Aimaretti et al, 2004;Bondanelli et al, 2004) demonstrate that cortical TBI can have substantial effects on the expression of the GH system, supporting clinical studies and replicating the results in an animal model of CNS injury.…”
Section: Kasturi and Stein Discussionsupporting
confidence: 54%
“…Other signaling mechanisms could include trans-synaptic (Koliatsos et al, 2004) as well as anterograde and retrograde neuronal degeneration from the site of injury to the more distal sites (Sorensen et al, 1996;Bechmann and Nitsch, 1997), also eventually affecting some of the endocrine functions. While we know something about the effects of TBI on endocrine function based on human studies (Ceballos, 1966;Agha et al, 2004aAgha et al, , 2004bAgha et al, , 2005aAgha et al, , 2005bAimaretti et al, 2004Aimaretti et al, , 2005bBondanelli et al, 2004;Herrmann et al, 2006;Powner et al, 2006;Schneider et al, 2006;Tanriverdi et al, 2006), there is still some uncertainty about the mechanisms by which long-term alterations in the endocrine system (like suppression of serum GH in TBI subjects) evolve over time, and whether such changes could be prevented by therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, other authors demonstrated a high prevalence of diabetes insipidus during the acute phase post-TBI in patients admitted to a neurosurgical center (22 -26%) (49,69) and in patients with head injury damaging the chiasm (37%) (70). However, diabetes insipidus is frequently transient and can spontaneously disappear within a few days or up to 1 month (66,70,71) after the acute event, as confirmed by its low prevalence (0 -6.9%) in patients evaluated after months or years following TBI (5,6,69).…”
Section: Consequences Of Tbimentioning
confidence: 99%
“…Musculoskeletal problems are also common, with an incidence of fractures of approximately 30% (8). Neuroendocrine dysfunction occurs in approximately 40% of patients with TBI (5,6,30). Medical complications occur not only in the immediate postinjury period with implications for early rehabilitation, but may persist for many months or become chronic.…”
Section: Consequences Of Tbimentioning
confidence: 99%
See 1 more Smart Citation